2020
DOI: 10.1093/pcp/pcaa071
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis SMN2/HEN2, Encoding DEAD-Box RNA Helicase, Governs Proper Expression of the Resistance Gene SMN1/RPS6 and Is Involved in Dwarf, Autoimmune Phenotypes of mekk1 and mpk4 Mutants

Abstract: In Arabidopsis thaliana, a mitogen-activated protein kinase pathway, MEKK1–MKK1/MKK2–MPK4, is important for basal resistance and disruption of this pathway results in dwarf, autoimmune phenotypes. To elucidate the complex mechanisms activated by the disruption of this pathway, we have previously developed a mutant screening system based on a dwarf autoimmune line that overexpressed the N-terminal regulatory domain of MEKK1. Here, we report that the second group of mutants, smn2, had defects in the SMN2 gene, e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Notably, we could also reannotate the chromosomal region around RPS6 itself. The extreme autoimmunity phenotypes of NMD mutants and mitogen-activated kinase pathway mutants require RPS6 but the mechanisms involved are not understood (Gloggnitzer et al, 2014;Takagi et al, 2020).…”
Section: Nlrs Are Major Targets Of Fpa-sensitive Alternative Poly(a) Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we could also reannotate the chromosomal region around RPS6 itself. The extreme autoimmunity phenotypes of NMD mutants and mitogen-activated kinase pathway mutants require RPS6 but the mechanisms involved are not understood (Gloggnitzer et al, 2014;Takagi et al, 2020).…”
Section: Nlrs Are Major Targets Of Fpa-sensitive Alternative Poly(a) Site Selectionmentioning
confidence: 99%
“…For example, null mutants defective in nonsense mediated RNA decay (NMD) are lethal in Arabidopsis because they trigger NLR RPS6-dependent autoimmunity (Gloggnitzer et al, 2014). Conversely, mutations in the RNA exosome, which degrades RNAs in a 3′ to 5′ direction, suppress RPS6-dependent autoimmune phenotypes (Takagi et al, 2020). Fine tuning of different levels of NLR control may be integrated to produce quantitative patterns of disease resistance (Corwin and Kliebenstein, 2017), but our understanding of how this occurs globally is fragmentary and incomplete (Adachi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, our reannotation of the RPS6 locus is essential to understand the recurring role of RPS6 in autoimmunity. The autoimmune phenotypes of mutants defective in NMD or the mitogen-activated kinase pathway are RPS6 dependent, but the mechanisms involved are unclear (Gloggnitzer et al, 2014;Takagi et al, 2020). We found that RPS6 is transcribed through a previously unrecognised downstream gene that encodes an RPS6like TIR domain.…”
Section: Widespread Control Of Nlr Transcription Termination By Fpamentioning
confidence: 84%
“…Notably, we could also reannotate the chromosomal region around RPS6 itself. The extreme autoimmunity phenotypes of NMD mutants and mitogen-activated kinase pathway mutants require RPS6 but the mechanisms involved are not understood (Gloggnitzer et al, 2014;Takagi et al, 2020). Nanopore DRS indicates that the 3′UTR of RPS6 is complex, with multiple splicing events and poly(A) sites (Figure 3C).…”
Section: Nlrs Are Major Targets Of Fpa-dependent Poly(a) Site Selectionmentioning
confidence: 99%
“…Incidentally, in addition to facilitation of eRNA detection, an assessment of the relevance of nuclear exosomal RNA decay for PTI activation has merit on its own. In yeast, there is evidence that mechanisms of alternative transcription termination coupled to exosome-mediated nuclear pre-mRNA decay contribute to shape rapid reprogramming of gene expression in response to stress (Bresson et al 2017), and a recent study in Arabidopsis provided an example of requirement of HEN2 for expression of a specific intracellular immune receptor (RPS6) (Takagi et al 2020), belonging to the Nucleotide Binding-Leucine Rich Repeat (NB-LRR)-class well known to be induced in PTI (Navarro et al 2004).…”
Section: Introductionmentioning
confidence: 99%